Nicotinamide Riboside Augments the Aged Human Skeletal Muscle NAD+ Metabolome and Induces Transcriptomic and Anti-inflammatory Signatures - Elhassan, Yasir S.; Kluckova, Katarina; Fletcher, Rachel S.; Schmidt, Mark S.; Garten, Antje; Doig, Craig L.; Cartwright, David M.; Oakey, Lucy; Burley, Claire V.; Jenkinson, Ned; Wilson, Martin; Lucas, Samuel J.E.; et al. (Cell reports (Cambridge), 2019)
Nicotinamide adenine dinucleotide (NAD+) is modulated by conditions of metabolic stress and has been reported to decline with aging in preclinical models, but human data are sparse. Nicotinamide riboside (NR) supplementation ameliorates metabolic dysfunction in rodents. We aimed to establish whether oral NR supplementation in aged participants can increase the skeletal muscle NAD+ metabolome and if it can alter muscle mitochondrial bioenergetics. We supplemented 12 aged men with 1 g NR per day for 21 days in a placebo-controlled, randomized, double-blind, crossover trial. Targeted metabolomics showed that NR elevated the muscle NAD+ metabolome, evident by increased nicotinic acid adenine dinucleotide and nicotinamide clearance products. Muscle RNA sequencing revealed NR-mediated downregulation of energy metabolism and mitochondria pathways, without altering mitochondrial bioenergetics. NR also depressed levels of circulating inflammatory cytokines. Our data establish that oral NR is available to aged human muscle and identify anti-inflammatory effects of NR. [Display omitted] •NR supplementation in aged subjects augments the skeletal muscle NAD+ metabolome•NR supplementation does not affect skeletal muscle mitochondrial bioenergetics•NR supplementation reduces levels of circulating inflammatory cytokines Elhassan et al. show that oral nicotinamide riboside increases the NAD+ metabolome in aged human skeletal muscle, without apparently altering mitochondrial bioenergetics. Measures of muscle and whole-body metabolism are also unchanged. Nicotinamide riboside reduces the levels of circulating inflammatory cytokines. Studies in relevant human disease models are warranted.